Global positioning system on cadastral survey of Nepal (Journal on Geoinformatics, Nepal, 2003)
Preparation of a series of cadastral maps and distribution of the land ownership certificates to each landowner of the whole kingdom of Nepal has been completed recently. However, half of the cadastral mapping of the country was carried out without the national coordinate system references and attention has given to map the private cultivated land, public land and government land with settlements during the cadastral surveying and mapping of the country. During the cadastral mapping of the country, it was realized that a national system of geodetic network of different order of ground control is required to prepare the large-scale map of the whole of the kingdom of Nepal. Everest spheroid 1830 and UTM (modified with three degree zone) projection system was selected for the geodetic reference and the higher order and lower order geodetic control networks was established with the traditional geodetic survey equipment i.e., theodolite and distance meter.This paper describes the observation procedure and the adjustment results with the accuracy standard of the geodetic control network of Nepal established in different time using different types of equipment and techniques. Attempt has been made to give some idea on theuse of Global Positioning System GPS control network extension for the production of large-scale cadastral plan of the country. A pilot project was selected to evaluate the results of the GPS techniques with that of the traditional theodolite and distance meter techniques for the control points extension of the large scale cadastral mapping of the densely populated area of the country.